Breastfeeding motivation in Pomerania: Survey of neonates in Pomerania (SNiP-Study). Issue 1 (December 2016) - Lange, Anja; Nautsch, Anke; Weitmann, Kerstin; Ittermann, Till; Heckmann, Matthias
Abstract Background The Nationale Stillkommission was founded in Germany in 1994 to increase the acceptance of breastfeeding as the primary means of infant nutrition. Scientific studies like "Stillen und Säuglingsernährung (SuSe-Studie)", and regional studies in Bavaria, Freiburg, Hamburg, and Berlin demonstrated breastfeeding initiation rates of 90 to 95%, but the total breastfeeding rate decreased to 25–61% after infants were 6 months old. One predictor of breastfeeding duration may be maternal motivation. The present study aimed to describe breastfeeding motivation. Methods We analysed data collected in 2004–2008, during a previous study, the Survey of Neonates in Pomerania (SNiP). We retrieved data regarding maternal breastfeeding motivation, family environment, and socioeconomic factors. We constructed a quantitative breastfeeding-motivation score to identify factors involved in maternal breastfeeding. Results Ninety five percent of mothers who gave birth in the study period and area provided information in the survey. The breastfeeding initiation rate was 88.4%. Mothers' intentions to provide exclusive breastfeeding (only breast milk, no other liquids or infant formula) increased linearly from 71.9% in 2005 to 76.8% in 2008. Women motivated to provide exclusive breastfeeding were, on average, older, primiparous, and able to deliver spontaneously more often than women with less breastfeeding motivation. Furthermore, women with no motivation to provide exclusive breastfeeding and women that intended to provide breastfeeding combined with a complementary nutrition source had visited prenatal classes less frequently, had lower levels education, had lower average incomes, had a German nationality more often, and used tobacco more often than women motivated to provide exclusive breastfeeding. Conclusions Breastfeeding intentions increased during the SNiP Study. This study identified several factors that might serve for targeted breastfeeding promotion in mothers younger than 25 years, mothers with low education, and multiparous mothers or women who have received a caesarean section. Furthermore, breastfeeding motivation might be enhanced during pregnancy and/or after delivery by providing prenatal classes.